PENGELOLAAN PRODUKSI MAKANAN UNTUK MENCIPTAKAN KEBERLANJUTAN INDUSTRI PERHOTELAN BERBASIS BISNIS HIJAU - Fitriana Fitriana; Pipin Kusumawati; Tri Eko Yudiandri; Michelle; Nia Astri Hermantyo; Muhammad Maulidvio Apriliana; Agung Sulistyo (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
Tourism development has a positive impact on the growth of its supporting industries. As a tourism supporter, hotels play a significant role in supporting tourists. Appropriate hotel management strategies must be implemented, reflecting the concept of green business. One effort is to consider the measurable amount of food consumption and production. Hotel managers do not fully implement the various opportunities the green business concept presents. Several obstacles arise, such as a lack of knowledge, innovation in food production management, and the ability to reduce food waste. This study investigates hotel management in producing food and reducing food waste to create a sustainable green business. A qualitative method using an interpretive approach was used in this study. Several hotels were selected as research objects, including: Hotel Cakra Kembang (best reviewed hotel), Greenhost Boutique Hotel (eco-green concept), and @HOM Premiere Hotel (best traveler's choice). These hotels have received various awards related to the green concept. The Miles Huberman method and triangulation were chosen as data analysis and validation techniques. The study results indicate that business managers must encourage food production savings without compromising service quality. Attention needs to be strengthened with management's ability to manage raw material stock, communicate with suppliers, develop business models, serve food, and predict guest attendance.